A survey for cognitive radio (CR) networks - Bataihah, Khalaf; Al_Issa, Huthaifa; Abdalhaliem, Laith (International Journal of Engineering & Technology, 2019)
Fixed spectrum allocation policy in the wireless networks leads to variations in the spectrum utilization of the allocated spectrum. This variation ranges from 15% to 85%, with high variance in time and geographical area in a random manner. However, the spectrum scarcity, the new technologies which provide high data rate but need more bandwidth, the new demand of lower cost per bit, and the in-efficiency in the spectrum bands all these problems can be addressed using the Cognitive Radio (CR) technology. In this paper, the CR aspects and functionalities are discussed, a brief discussion about the Medium Access Control (MAC) protocol design for a Cognitive Radio Network (CRN) is introduced, and the main critical CR issues as well (including heterogeneity induced problem, multichannel spectrum sensing, Common Control Channel (CCC) problem, spectrum mobility, and the self organization schemes in the CR functionalities).Â Â Â